The Transformation of the Functions and Architectural Values of the Medan Post Office as a Cultural Heritage Site in Medan City - Lister Eva Simangunsong; Rieke Corry Br Tarigan; Doly Simarmata; Dea Hutapea; Oktavina Sijabat (Medan Resource Center, 2026)
The Medan Post Office, currently known as Pos Bloc Medan, is one of the most prominent Dutch colonial heritage buildings in North Sumatra, possessing significant historical, architectural, and cultural value. Built in 1909 and inaugurated in 1911, the building originally served as a center for postal and communication services during the colonial period. This study aims to examine the historical development of the Medan Post Office, analyze its colonial architectural characteristics, and explore its functional transformation into Pos Bloc Medan as a strategy for cultural heritage preservation in Medan. This research employed a qualitative descriptive method, with data collected through literature review, observation, and documentation, and analyzed using the Miles and Huberman model. The findings indicate that the Medan Post Office exhibits a hybrid colonial architectural style that combines European design elements with adaptations to tropical environmental conditions. The study further reveals that transforming the building into Pos Bloc Medan has preserved its historical and architectural authenticity while introducing new functions as a creative public space, community center, and platform for local economic activities. This transformation represents a successful implementation of adaptive reuse, demonstrating that heritage conservation can remain relevant to contemporary urban needs without compromising historical values.